The effect of two different health messages on physical activity levels and health in sedentary overweight, middle-aged women - Ho Suleen; Cheng Cheryl; Pal Sebely (BMC, 2011)
Abstract Background Most public health guidelines recommend that adults need to participate in 30 minutes of moderate intensity physical activity on most days of the week to maintain good health. Achieving the recommended 30 minutes of exercise a day can be difficult in middle aged, overweight women. This 12 week study evaluated whether a 10,000 steps per day message was more effective than a 30 minutes a day message in increasing physical activity in low active, overweight women. Methods Thirty participants were randomized into 2 groups: Group 1 was asked to undertake 30 minutes of walking/day, whereas Group 2 was asked to accumulate 10,000 steps/day using their pedometers. Results Results showed that there were no changes in anthropometric and blood pressure measures between or within groups. However, the 10,000 step and the 30 minutes groups' daily average number of steps/day were significantly higher than baseline at week 6 (p = 0.038 and p = 0.039 respectively) and at week 12 (p = 0.028 and p = 0.038 respectively). At week 12, the 10,000 steps group were taking an average of 4616 steps per day more (43% increase) than at baseline and the 30 minutes group were taking an average of 2761 steps per day more (35% increase) than at baseline. There was a significant difference in the number of steps with the 10,000 steps group versus 30 minutes group at 12 weeks (p = 0.045). Conclusions This study found that low active, overweight women undertook significantly more physical activity when they had a daily 10,000 step goal using a pedometer, than when they were asked to achieve 30 minutes of walking/day. Therefore we suggest that a public health recommendation of "10,000 steps/day", rather than the "30 min/day" could be applied to promote increased physical activity in sedentary middle aged women.